Depletion of T regulatory cells through selection of CD127-positive cells results in a population enriched in memory T cells: implications for anti-tumor cell therapy - Soumia Touil; Michelle Rosenzwajg; Dan Avi Landau; Philippe Le Corvoisier; Charlotte Frédéric; David Klatzmann; Sébastien Maury; José L. Cohen (Haematologica, 2012)
Background Donor lymphocyte infusions can induce remissions in patients with relapse after allogeneic hematopoietic stem cell transplantation. Nevertheless, some grafted patients never display any signs of alloreactivity, either following allogeneic hematopoietic stem cell transplantation or after donor lymphocyte infusions. Consequently, they do not develop graft-versus-host disease and frequently do not respond to donor lymphocyte infusions. In a recently published clinical trial, we observed that elimination of CD4+CD25+Foxp3+ natural regulatory T cells from the donor lymphocyte product could improve alloreactivity and the associated anti-tumor effect in a small proportion of patients with relapsed hematologic malignancies. Here, we aimed to improve the effect of donor lymphocyte infusion by modifying the procedure for depletion of T regulatory cells.Design and Methods We directly compared depletion of regulatory T cells from human peripheral blood mononuclear cells achieved by selection of CD127-positive cells or by selection of CD25-negative cells. We tested the manipulated products (i) in vitro in mixed lymphocyte reactions and against pathogen-derived recall antigens and (ii) in vivo in experimental graft-versus-host disease.Results In vitro, we found that depletion of regulatory T cells through CD127 positive selection improved both alloreactive and pathogen-specific immune responses. In vivo, we observed accelerated donor T-cell division and enhanced graft-versus-host disease due to efficient regulatory T-cell depletion accompanied by enrichment in memory T cells.Conclusions Our results show that the strategy of CD127 positive selection is an efficient way of eliminating regulatory T cells from donor lymphocyte infusions and improves alloreactivity. This supports the investigation of CD127 positive selection in place of elimination of CD25-positive cells for clinical applications.